Formulation And Evaluation Of Self Emulsifying Drug Delivery System For Poorly Water Soluble Drug - Tiwari, Pooja; Dubey, Ragvendra; Baraskar, Ayushi (Journal of Neonatal Surgery, 2025)
By enhancing NVP's solubility, dissolution rate, and diffusion profile, the current work aimed to develop and optimize Posaconazole (PN) self-emulsifying drug delivery systems (SEDDS) to improve oral absorption. When added to the aqueous phase with little agitation, SEDDS—isotropic mixes of oil, surfactant, co-surfactant, and medication—form an oil-in-water microemulsion